Q.
f(p) = 1x + 2x + 3x + 4x + 5x + 6x
f(60) =
--
:v
[tex].[/tex]
f(p) = 1x + 2x + 3x + 4x + 5x + 6x
f(60) =
--
:v
[tex].[/tex]
Jawaban:
1.260
Penjelasan dengan langkah-langkah:
f(x) = 1x + 2x + 3x + 4x + 5x + 6x
= 21x
f(60) = 21(60)
= 21 × 6 × 10
= 126 × 10
= 1.260
f(P) = 1x + 2x + 3x + 4x + 5x + 6x
f(60) = 1(60) + 2(60) + 3(60) + 4(60) + 5(60) + 6(60)
f(60) = 60 + 120 + 180 + 240 + 300 + 360
f(60) = 180 + 180 + 240 + 300 + 360
f(60) = 360 + 240 + 300 + 360
f(60) = 600 + 300 + 360
f(60) = 900 + 360
f(60) = 1.260